2017
DOI: 10.3389/fpls.2017.01800
|View full text |Cite
|
Sign up to set email alerts
|

QTL Mapping of Grain Zn and Fe Concentrations in Two Hexaploid Wheat RIL Populations with Ample Transgressive Segregation

Abstract: More than 50% of undernourished children live in Asia and more than 25% live in Africa. Coupled with an inadequate food supply, mineral deficiencies are widespread in these populations; particularly zinc (Zn) and iron (Fe) deficiencies that lead to retarded growth, adverse effects on both the immune system and an individual's cognitive abilities. Biofortification is one solution aimed at reducing the incidence of these deficiencies. To efficiently breed a biofortified wheat variety, it is important to generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
58
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 38 publications
15
58
3
Order By: Relevance
“…These loci coincided with the loci identified in our study, on chromosomes 5A (AX-110931014, 650.24Mb), 6B (AX-109538092, 708.67Mb), and 7A (AX-111012263, 261.69Mb). Similarly, in a study conducted on a hexaploid wheat RIL, populations were identified five loci on chromosomes 1B, 2B, 3A, 3B, and 6A associated with Zn grain accumulation and explaining from 9% to 15% of the phenotypic variation [31]. In this study, we also identified 7 unique loci in 1B, 2B (2 loci), 3A, 3B (2 loci), and 6A, which could be associated with the QTL in the hexaploid bread wheat population [31].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…These loci coincided with the loci identified in our study, on chromosomes 5A (AX-110931014, 650.24Mb), 6B (AX-109538092, 708.67Mb), and 7A (AX-111012263, 261.69Mb). Similarly, in a study conducted on a hexaploid wheat RIL, populations were identified five loci on chromosomes 1B, 2B, 3A, 3B, and 6A associated with Zn grain accumulation and explaining from 9% to 15% of the phenotypic variation [31]. In this study, we also identified 7 unique loci in 1B, 2B (2 loci), 3A, 3B (2 loci), and 6A, which could be associated with the QTL in the hexaploid bread wheat population [31].…”
Section: Discussionmentioning
confidence: 87%
“…Many QTLs for Zn accumulation in grains have been detected by bi-parental linkage mapping [19,23,31,32,37], which allowed a comparison between known QTLs and loci identified in the present study. In the current study, 29 significant non-redundant loci were scattered across all wheat genome (except on chromosomes 2A, 4D, 5D, 7B, and 7D).…”
Section: Discussionmentioning
confidence: 97%
“…QTLs for grain zinc and iron have also been mapped in populations derived from crosses between T. boeoticum and T. monococcum [106], durum wheat and wild emmer [64] synthetic hexaploid wheat and T. spelta [107,108,109]. Tiwari et al [106] mapped 2 QTL for grain Fe on chromosomes 2A and 7A explaining 12.6 and 11.7% of phenotypic variation and 1 QTL for grain Zn on chromosome 7A explaining 18.8% of total phenotypic variation, using a RIL population derived from a cross between T. boeoticum accession 'pau5088' and T. monococcum accession 'pau14087'.…”
Section: Qtls For Grain Fe and Zn Concentration In Wheatmentioning
confidence: 99%
“…Tiwari et al [106] mapped 2 QTL for grain Fe on chromosomes 2A and 7A explaining 12.6 and 11.7% of phenotypic variation and 1 QTL for grain Zn on chromosome 7A explaining 18.8% of total phenotypic variation, using a RIL population derived from a cross between T. boeoticum accession 'pau5088' and T. monococcum accession 'pau14087'. Recently in 2017, Crespo-Herrera et al [108] identified several significant QTLs with a region named as nQGZn.cimmyt-7B_1P2 on chromosome 7B explaining the largest proportion (32.7%) of total phenotypic variance for GZn and one QTL on chromosome 4A (QGFe.cimmyt-4A_P2), explaining the largest (21.14%) proportion of phenotypic variance of the GFe in two RIL populations derived from T. spelta L. and synthetic hexaploid wheat crosses. In other study, Krishnappa et al [109] mapped four QTLs, explaining 20 % of total phenotypic variation and five QTLs, explaining 32% of total phenotypic variation for GFe and GZn, respectively using a RIL population derived from a cross between an Indian wheat variety 'WH542' and a synthetic derivative.…”
Section: Qtls For Grain Fe and Zn Concentration In Wheatmentioning
confidence: 99%
“…Plants growing in soil with <1 μg g −1 may not provide an adequate amount of Zn for people with plant‐based diets. Since 2000, efforts to biofortify food crops with micronutrients have led to better understanding of the physiological, genetic, and molecular basis of Zn accumulation in grain (Crespo‐Herrera, Velu, Stangoulis, Hao, & Singh, 2017). In addition, the effects of agronomic management and environmental situations on Zn uptake, translocation, and loading into grains have been illuminated (Velu, Ortiz‐Monasterio, Cakmak, Hao, & Singh, 2014).…”
Section: Introductionmentioning
confidence: 99%